PENGUJIAN VALIDITAS DAN RELIABILITAS SKALA DUKUNGAN IMAN - Suwartono, Christiany; Suhendra, Junianawaty; Soeherman, Sylvia; Mamahit, Aileen P. (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2019)
Abstract ? The formation of faith in adolescents and young people is rooted in their interaction with parents, both father, and mother, as well as friends. Adolescence and young adulthood are periods of seeking faith in various aspects of life. However, there has not been a measurement of the extent to which adolescents and young people regard parents and friends as role models of their faith. This study was aimed to the Perceived Faith Support - Parents and Friends Scale to be the Scale of Faith Support. The study was conducted through convenience sampling, involving 1,390 participants from three major islands in Indonesia. The results of this adaptation proved to be reliable with internal consistency methods, especially Cronbach's Alpha and to be valid with factor analysis methods. Validation with age criteria is proven by the support of faith from the father and mother, but not with friends. The Faith Support Scale is argued to be fit for both theoretical and practical purposes. The development and application of this scale are further discussed. Abstrak ? Pembentukan iman pada remaja dan kaum muda merupakan hasil interaksi mereka dengan orang tua, baik ayah maupun ibu, juga teman. Masa remaja dan kaum muda merupakan masa pencarian keyakinan (iman) di berbagai aspek kehidupan. Namun, belum ada pengukuran mengenai sejauh mana remaja dan kaum muda menganggap orang tua dan teman sebagai teladan iman dirinya. Studi ini bertujuan untuk mengadaptasi skala Perceived Faith Support ? Parents and Friends menjadi Skala Dukungan Iman. Penelitian dilakukan dengan teknik convenience sampling dan melibatkan 1,390 partisipan dari tiga pulau besar di Indonesia. Hasil adaptasi ini terbukti reliabel dengan metode konsistensi internal, khususnya Cronbach?s Alpha dan valid dengan metode faktor analisis. Validasi dengan kriteria usia terbukti pada dukungan iman dari ayah dan ibu, namun tidak dengan teman. Skala Dukungan Iman ini siap digunakan dalam konteks penelitian maupun praktis. Pengembangan dan aplikasi skala ini dibahas lebih lanjut.